Effect of Temperatures on Cyclic Fatigue Resistance of 3 Different Ni-Ti Alloy Files - Sirawut Hiran-us; Sarita Morakul (Elsevier, 2023)
ABSTRACT: Objective: The aim of this study was to investigate and compare the effect of temperature on the cyclic fatigue resistance of conventional (ProTaper Universal [PTU]), Gold-Wire (ProTaper Gold [PTG]), and Fire-Wire (EdgeTaper Platinum [ETP]) nickel-titanium alloy files. Method: Twenty files from each system were tested for cyclic fatigue resistance in an artificial canal model. The experiments were performed at room temperature and body temperature in controlled temperature water. Magnified videos were recorded using a dental operating microscope integrated camera during testing to detect file fracture. The number of cycles to failure (NCF) was calculated. The type of failure was investigated macroscopically and microscopically with a dental operating microscope and scanning electron microscope, respectively. Result: The NCF at room temperature was significantly higher compared with body temperature in each system (P < .001). Compared at the same temperature, the ETP group demonstrated the highest NCF, followed by the PTG and PTU groups (P < .001). All files demonstrated cyclic fatigue failure macroscopically and microscopically. Conclusions: The 3 alloy files were affected by temperature. The cyclic fatigue resistance was reduced at the higher temperature and increased at the lower temperature. If the files are geometrically identical, files made of Fire-Wire are preferred compared with Gold-Wire and conventional nickel-titanium alloys based on cyclic fatigue resistance.